NEEDS ANALYSIS OF THE NATION'S CHARACTER-FILLED TEXTS IN INDONESIAN TEACHING MATERIALS - Defina Defina (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2017)
The aim of this study analyzed the need for character-filled texts in Indonesian language teaching materials in IPB and identify other character values needed. The method is R & D with the concepts of Dick and Carey and Borg and Gall. The result,  the value of characters sourced from the heart: obedient rules, honesty and order, religious and pious, fair, orderly, responsible, and empathetic; comes from though: creative, intelligent, critical, innovative and oriented ipteks; sourced from kinesthetic: persistent, friendly, cheerful, clean, sportive, and cooperative; sourced from taste, proud to use the Indonesian language, love the homeland, and nationalist. Proposed, there is additional value of confident and anticorruption character. Conclusion, it is necessary to develop teaching material of Indonesian language that contains the values of nation character.Keywords: needs analysis, Indonesian language teaching materials, character valuesANALISIS KEBUTUHAN TERHADAP TEKS-TEKS BERMUATAN KARAKTER BANGSA DALAM MATERI AJAR BAHASA INDONESIAAbstrakTujuan penelitian ini menganalisis kebutuhan terhadap teks-teks bermuatan nilai-nilai karakter dalam materi ajar bahasa Indonesia di IPB dan mengidentifikasi nilai-nilai karakter lain yang dibutuhkan. Metodenya adalah R&D dengan konsep Dick dan Carey  dan  Borg dan Gall. Hasilnya,  nilai karakter yang bersumber dari olah hati taat aturan, kejujuran dan ketertiban, beriman dan bertaqwa, adil, tertib,  bertanggung jawab, dan  berempati; bersumber dari olah pikir kreatif, cerdas, kritis, inovatif dan  berorientasi ipteks; bersumber dari olah raga gigih, bersahabat, ceria, bersih, sportif, dan kooperatif; bersumber dari olah rasa-karsa, bangga  menggunakan bahasa Indonesia, cinta tanah air, dan nasionalis. Usulan, ada tambahan nilai karakter percaya diri dan antikorupsi. Kesimpulan, perlu dikembangkan materi ajar bahasa Indonesia yang memuat nilai-nilai karakter bangsa.Kata kunci: analisis kebutuhan, materi ajar bahasa indonesia, nilai-nilai karakter